Lattice Boltzmann-based numerical analysis of nanofluid natural convection in an inclined cavity subject to multiphysics fields - Ibrahim, Muhammad; Berrouk, Abdallah S.; Saeed, Tareq; Algehyne, Ebrahem A.; Ali, Vakkar (Scientific reports, 2022)
This research conducts a study of natural convection heat transfer (NCHT) in a nanofluid under a magnetic field (MF). The nanofluid is in a cavity inclined at an angle of 45°. The MF can take different angles between 0° and 90°. Radiative heat transfer is present in the cavity in volumetric form. There are two hot semicircles, similar to two half-pipes, on the bottom wall. The top wall is kept cold. The side walls and parts of the bottom wall, except the pipes, have been insulated. The lattice Boltzmann method has been used for the simulation. The studied parameters are the Rayleigh number (in the range 10 3 –10 6 ), magnetic field angle, radiation parameter (in the range 0–2), and nanoparticle volume fraction (in the range 0–5%). The generated entropy has been studied as the NCHT. The results indicate that adding nanoparticles improves heat transfer rate (HTR). Moreover, the addition of volumetric radiation to the cavity enhances the Nusselt number by 54% and the generated entropy by 12.5%. With an augmentation in the MF angle from 0° to 90°, HTR decreases and this decrease is observed mostly at higher Rayleigh numbers. An augmentation in the Ra increases NCHT and entropy generation. Indeed, a rise in the Ra from 10 3 to 10 6 increases HTR by almost sixfold.